Formative Assessment in Inclusive Mathematics Education in Secondary Schools: A Systematic Review - Fynn Töllner; Poldi Kuhl; Michael Besser (Education Sciences)
Formative assessment is a way to individualize learning and tailor instruction to learners’ specific needs. These practices are particularly relevant due to the increasing heterogeneity resulting from the transition to an inclusive education system and the associated question of how teachers can deal with this rise in heterogeneity. However, there is no systematic interlinking between these two areas vis-à-vis mathematics secondary education. Therefore, little is known about how the benefits of formative assessment can be achieved in inclusive secondary mathematics education, with its heterogeneous learning groups. Accordingly, we searched the FIS Bildung, PsycInfo, and PSYNDEX-plus Tests databases, resulting in 14 articles addressing either formative assessment in general or diagnostics and feedback as components of formative assessment, particularly in inclusive secondary mathematics education. These publications were coded and analyzed according to their affiliation with one of the key components or formative assessment in general. Results indicate that, first, diagnostics must be highly individualized while considering contextual factors to be accurate; second, teachers should be advised on how to proceed with the diagnosed issues; and, finally, teachers should provide their students with frequent, easily accessible feedback. Furthermore, we identify productive directions for future research, along with implications for inclusive everyday teaching, and discuss limitations.